95.7k views
4 votes
Solve by elimination.

X + y =4
3x + 3y =12

User Grimsock
by
4.5k points

1 Answer

1 vote

Answer:

Infinite solutions

Explanation:

X + y =4

3x + 3y =12

Multiply the first equation by -3 to eliminate x

-3(X + y =4)

-3x-3y =-12

Now add this to the second equation

-3x-3y =-12

3x + 3y =12

----------------------

0=0

This is always true. That means there are infinite solutions.

User CamelCaseCowboy
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.